Identification of a resveratrol tetramer as a potent inhibitor of hepatitis C virus helicase. (25th November 2015) - Lee, Sungjin; Yoon, Kee Dong; Lee, Myungeun; Cho, Yoojin; Choi, Gahee; Jang, Hongje; Kim, BeomSeok; Jung, Da‐Hee; Oh, Jin‐Gyo; Kim, Geon‐Woo; Oh, Jong‐Won; Jeong, Yong‐Joo; et al.
Abstract : Background and Purpose: Hepatitis C virus (HCV) infection is responsible for various chronic inflammatory liver diseases. Here, we have identified a naturally occurring compound with anti‐HCV activity and have elucidated its mode of antiviral action. Experimental Approach: Luciferase reporter and real‐time RT‐PCR assays were used to measure HCV replication. Western blot, fluorescence‐labelled HCV replicons and infectious clones were employed to quantitate expression levels of viral proteins. Resistant HCV mutant mapping, in vitro NS3 protease, helicase, NS5B polymerase and drug affinity responsive target stability assays were also used to study the antiviral mechanism. Key Results: A resveratrol tetramer, vitisin B from grapevine root extract showed high potency against HCV replication (EC50 = 6 nM) with relatively low cytotoxicity (EC50 >10 μM). Combined treatment of vitisin B with an NS5B polymerase inhibitor (sofosbuvir) exhibited a synergistic or at least additive antiviral activity. Analysis of a number of vitisin B‐resistant HCV variants suggested an NS3 helicase as its potential target. We confirmed a direct binding between vitisin B and a purified NS3 helicase in vitro . Vitisin B was a potent inhibitor of a HCV NS3 helicase (IC50 = 3 nM). In vivo, Finally, we observed a preferred tissue distribution of vitisin B in the liver after i.p. injection in rats, at clinically attainable concentrations. Conclusion and Implications Vitisin B is one of the most potent HCV helicase inhibitors identified so far. Vitisin B is thus a prime candidate to be developed as the first HCV drug derived from natural products.